Question formation strategies in Kunuz Nubian - Abdel-Hafiz, Ahmed Sokarno (Technium Social Sciences Journal, 2020)
This is an analytical and descriptive study that is based on a general theoretical framework which can be characterized as “basic linguistic theory”. It aims to study Kunuz Nubian interrogative pronouns and question markers. Previous studies failed to pay adequate attention to these features. It is an attempt to characterize the strategies used in question formation and to identify the question markers. I argue that the question markers in this Nubian dialect fall into three sets: (a) the set of question markers -yaa, -naa, and -waa are used with sentences (non-copular construction) involving the neural marker -r-. (b) the set of questions markers that are used if the neural marker –r- is in a copular construction: -yaa, -re, -waa. (c) another set of question markers are attached to a declarative sentence in which the verb or copular verb is accompanied with the past tense morpheme. The study has also provided a list of interrogative pronouns that can occur with or without the question markers. Moreover, it has been shown that both compound and complex sentences are turned into interrogatives via the same question strategies used in simple sentences.